Metabolic and ventilatory changes in asthmatic patients during and after exercise. Issue 6 (November 1972) - Anderson, Sandra D.; Silverman, M.; Walker, S. R.
Abstract : Five asthmatic patients aged 25-30 years were studied during and after 6-8 minutes of steady exercise on both a bicycle ergometer and a treadmill. For each patient the duration of work, oxygen consumption, minute ventilation, and heart rate were similar in each form of exercise. During exercise all patients had an increase in peak expiratory flow rate. The blood lactate level was higher during bicycle exercise but arterial Pco 2 and pH fell to similar levels during both forms of exercise. There was a rise in arterial oxygen tension in four of the patients during exercise; in one subject arterial oxygen tension fell. Bronchoconstriction was greater following treadmill exercise in all subjects and was associated with an increase in ventilation/perfusion inequality, as shown by arterial hypoxaemia, an increase in alveolar-arterial oxygen tension gradients, and an increase in physiological dead space. In one subject whose PEFR fell to 25% of the predicted value Co 2 retention occurred. These changes are similar to those found in other forms of acute asthma. In one subject, during both forms of exercise the mixed expired Pco 2 was observed to be higher than the arterial Pco 2, thus giving a negative value for physiological dead space. This observation is discussed.